Advancement of Mean Codeword Lengths through Weighted Divergence Model - Om Parkash, Rakesh Kumar (International Journal of Advanced Science and Technology, 2020)
Entropy and divergence cooperate by performing an imperative assignment in manipulating various techniques for data compression and are made functional by acting as lower bounds to numerous mean codeword lengths existing in the literature. The present communication dealing with the investigations of a new weighted divergence and its applications for the growth of new codeword length and extraction of existing ones is an objective of our study. Moreover, this innovative study provides a deeper imminent and association flanked by weighted divergence measures and the codeword lengths. Keywords: Entropy, Weighted entropy, Divergence, Weighted divergence, Mean codeword length, Uniquely decipherable code.